Have We ARRIVEd at a New Normal?. Issue 1 (January 2019) - Breedlove, Ginger
Abstract : Publication of the ARRIVE trial of elective induction of labor for healthy low-risk nulliparous women has generated a lot of discussion and concern among childbearing women and those who care for them. Guest columnist Dr. Ginger Breedlove explains some of the issues and potential implications for clinical practice.